2017
DOI: 10.1111/luts.12156
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome Induced Bladder Cannabinoid Receptor Changes in the Fructose‐Fed Rats

Abstract: CB1/CB2 receptors mediate rat bladder relaxation through the PKA and K pathway. The CB1 receptor may play a more prominent role. The response is decreased in the FR bladder due to reduced expressions of the cannabinoid receptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
(61 reference statements)
0
10
0
Order By: Relevance
“…In such studies, there is notable inter- and intra-species variation in the outcome between mice ( Mus musculus ) and rats ( Rattus norvegicus ). Among rats, the most reliable strains are Sprague–Dawley (SD) rats and spontaneously hypertensive rats (SHR) [ 33 , 34 , 35 , 36 , 38 , 39 , 40 , 41 , 43 , 46 ]. Both strains can manifest the many characteristics of MetS with no serious inconsistencies or conflicts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In such studies, there is notable inter- and intra-species variation in the outcome between mice ( Mus musculus ) and rats ( Rattus norvegicus ). Among rats, the most reliable strains are Sprague–Dawley (SD) rats and spontaneously hypertensive rats (SHR) [ 33 , 34 , 35 , 36 , 38 , 39 , 40 , 41 , 43 , 46 ]. Both strains can manifest the many characteristics of MetS with no serious inconsistencies or conflicts.…”
Section: Resultsmentioning
confidence: 99%
“…These two studies were able to achieve all MetS determinant parameters, although they did not incorporate all aspects thereof, such as organ or tissue mass, caloric intake, blood glucose levels, and insulin resistance. However, Table 1 shows that a 60% fructose-based diet encompassed all categories of MetS and achieved all but one: increased BW, length, or abdominal circumference [ 21 , 35 , 39 , 40 , 45 ]. Of those five articles, only one reported visibly increased BW, but it was not statistically significant [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Inconsistent responses on TG concentration which have been reported in rats fed with HS diet in previous studies. Rats exposed to a high fructose diet showed a significant increased TG levels compared to the other exposed to a regular diet [7, 17, 18]. In contrast, other studies have reported no change in TG concentration in rats fed with high fructose diet for a short and long period [8, 19, 20].…”
Section: Discussionmentioning
confidence: 99%
“…Insulin is not only a hormone but also a growth factor ( Ikle and Gloyn, 2021 ), and fructose-fed rats often exhibit a greater increase in insulin than in glucose levels, possibly reflecting peripheral insulin resistance ( Chen et al, 2018 ). After having noticed a moderate to strong correlation of bladder enlargement with insulin levels in one study with fructose-fed rats ( r 2 = 0.5127), we performed a similar post-hoc analysis on the other five studies with available insulin data: all five studies including another study in fructose-fed rats exhibited very weak, and in one of them and in the pooled analysis of all studies numerically inverse correlations ( Figure 3 ; Table 3 ).…”
Section: Discussionmentioning
confidence: 99%